2009
DOI: 10.1016/j.adolescence.2009.11.004
|View full text |Cite
|
Sign up to set email alerts
|

Health‐risk behaviors in adolescents as indicators of unconventional lifestyles

Abstract: This study analyses the dimensions of health‐risk behaviors in adolescence. Based on the Theory of Problem Behavior, the study hypothesises that the structure of relations between risk behaviors may be explained in terms of their level of social transgression or unconventionality. With a sample of 771 adolescents, this study explores the association between the behaviors which, according to the WHO, have a greater impact on morbidity and mortality. The results of these analyses point to the existence of a late… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 65 publications
(67 reference statements)
0
10
0
2
Order By: Relevance
“…Among Brazilian adults, drinking alcohol and smoking were found as part of a risky lifestyle pattern, together with lack of physical activity and unhealthy diet intake,8 in contrast with our findings among adolescents. Among adults, drinking alcohol and smoking are common and socially accepted, while they are contesting or rule-breaking behaviours among adolescents 9. This may explain why our study found a problem-behaviour pattern with drinking alcohol and smoking together with aggressive behaviour and not in the compromising behaviour, which included unhealthy diet and sedentary behaviour.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…Among Brazilian adults, drinking alcohol and smoking were found as part of a risky lifestyle pattern, together with lack of physical activity and unhealthy diet intake,8 in contrast with our findings among adolescents. Among adults, drinking alcohol and smoking are common and socially accepted, while they are contesting or rule-breaking behaviours among adolescents 9. This may explain why our study found a problem-behaviour pattern with drinking alcohol and smoking together with aggressive behaviour and not in the compromising behaviour, which included unhealthy diet and sedentary behaviour.…”
Section: Discussionmentioning
confidence: 55%
“…The difference between these two risk-behaviour patterns may lie at the level of their social acceptability. According to the literature, violent behaviour, drug use and smoking are less socially acceptable behaviours among adolescents,9 and were captured by the problem-behaviour pattern, while the health-compromising diet and sedentary behaviours pattern brought together behaviours that represent harm to health but are not seen as unacceptable either by students or society, such as unhealthy food consumption and sedentary behaviour 9. Among Brazilian adults, drinking alcohol and smoking were found as part of a risky lifestyle pattern, together with lack of physical activity and unhealthy diet intake,8 in contrast with our findings among adolescents.…”
Section: Discussionmentioning
confidence: 99%
“…Estão relacionadas diretamente com a urbanização acelerada, migração interna, desigualdades sociais e marginalização, fatores indissociáveis da violência que acomete todas as faixas etárias, principalmente no sexo masculino, devido à maior exposição ao álcool, tabagismo, drogas, inserção no mercado de trabalho informal e atividades ilícitas. 17,18 Em hospitais norte-americanos os acidentes foram identificados como a principal causa de internação entre os adolescentes de 10 a 14 anos de ambos os sexos e para os rapazes com mais de 15 anos, enquanto que as complicações da gravidez determinaram a maioria das internações na faixa etária dos 15 aos 19 anos. 19 Achados semelhantes também foram relatados no Brasil, sendo identificadas as causas externas como a principal causa de mortalidade entre adolescentes, principalmente no sexo masculino e na faixa etária dos 15 aos 19 anos.…”
Section: Discussão Discussão Discussão Discussão Discussãounclassified
“…The World Health Organization defines violence as the use of physical force or real threat power against oneself, against another person, or against a group or community, which either results in or has any chance of resulting in injury, death, psychological harm, development disability, or deprivation [1, 2]; thus violent behavior can be considered as the behavior that leads the subject or community to commit violent acts.…”
Section: Introductionmentioning
confidence: 99%
“…A greater concern is the group of children and adolescents, they appear in the statistics as the most seriously injured and more murders of occurrences, as suggested by several studies in an attempt to expand the knowledge about the possible factors associated with physical fights among youngsters [14]. …”
Section: Introductionmentioning
confidence: 99%